Teacher learning from supplementary curricular materials: Shifting instructional roles. (July 2019) - Matewos, Ananya M.; Marsh, Julie A.; McKibben, Susan; Sinatra, Gale M.; Le, Q. Tien; Polikoff, Morgan S.
Abstract: This study sought to understand how teachers learn through the process of implementing supplementary curricula, and to what extent the use of curricular materials leads to changes in instructional approaches. Through implementing a STEM supplementary curricular unit aligned to NGSS, the researchers conducted multiple case studies to examine teacher learning and identified potential factors that mediated instructional change. Based on experiences of seven teacher participants, results showed different learning trajectories, wherein teachers either moved towards student-directed instructional roles or maintained teacher-directed roles. Doubt and self-questioning appear to be important mediating aspects of teacher self-reflection, which then impacts instructional role change. Highlights: Teachers enacted different instructional roles based on sensemaking of supplementary curricular demands. Learning trajectories emerged in which teachers either did or did not shift instructional roles. Instructional roles shifted towards student-centered practices or remained teacher-directed. Doubt induced from practice is an impetus for teacher self-reflection and potential role change.